Titanium Influence on the Microstructure of FeCrAl Alloys Used for 4R Generation Nuclear Power Plants - Geanta, Victor; Voiculescu, Ionelia; Stefanoiu, Radu; Jianu, Adrian; Milosan, Ioan; Stanciu, Elena Manuela; Pascu, Alexandru; Vasile, Ion Mihai (REVISTA DE CHIMIE, 2019)
4R generation nuclear power plants should work with metallic material of the highest quality, capable to resist in maximum safe conditions for 25-30 years. FeCrAl alloys are capable of such performance, because of the resistance to: oxidation at high temperatures, corrosion, erosion and penetrating radiations in liquid metal environments. In addition, such materials are capable of forming on their surface some oxide layers, textured and self-renewable, with high adhesion to metallic substrates. These properties can be improved by microalloying with metal elements such as Ti, Zr, Y, Hf in amounts of 1 to 3%. These chemical elements have high affinity to oxygen, being able to stabilize the structure of the superficial layer of oxide (alumina) and to increase adhesion to the metallic substrate. The FeCrAl alloys microalloyed with titanium were obtained in a VAR (Vacuum Arc Remelting) equipment in argon atmosphere (99.99% purity). There were obtained three batches microalloyed with 0.5%, 1% and 1.5% titanium, preserving the same Fe-14Cr-5Al metal matrix. In order to determine the chemical composition of the oxide layer and of the sample bulk, the EDAX analysis was performed. Microstructural features were revealed using SEM analysis. The results showed the capacity of the FeCrAl alloy to form oxide layers, with different textures and rich in elements such as Al and Ti. The compositional analysis performed on FeCrAl samples microalloyed with 0.5, 1.0 and 1.5% Ti in the central zone shows a relatively similar composition compared to the technological calculations made, reflecting the homogeneity of the alloy. The microhardness measurements performed on the cross sections of the metallic samples attest values in the range 163-183 HV0.2, falling within the normal range for these materials. These values are influenced by the presence of the alloying elements in the metallic matrix and by the homogeneous arrangement of constituents.
Keywords: FeCrAl alloys; titanium; chemical composition; microhardness; microstructure.